Inflasi Berdasarkan Pandangan M. Umer Chapra - Muhammad Ridha (Universitas Islam Negeri Sumatera Utara, 2019)
According to Islamic economists, inflation has very bad effect on the economy because it disruptions of money function, weakens of saving’s spirit, decreases the production of goods, and weakens of purchasing power. Inflation also attracted the attention of M. Umer Chapra as a Muslim economist. This study to analyze M. Umer Chapra's opinion on inflation. This research with qualitative approach of historical research, which examines history of the character which includes ideas, thoughts, and things that influence the formation of his thoughts. Data collection methods is using library research with the object about Chapra’s thoughts relating to inflation, traced through his works. Chapra thought is a blend of traditional science, religion and modern economics. The results concluded that his thinking was dominated by macroeconomics because he was involved in the world economy, monetary policy, Islamic financial institutions which were more emphasized by the central bank, policies and inflation problems. Chapra's view of efforts to suppress inflation is the need for price stability and strategy. The disadvantage is that in a tolerant attitude towards western financial instruments, it must emphasize moral improvement for the course of fair economy as the solution to the failure of the capitalist and socialist economic systems.